Termite resistance of Melaleuca cajuputi wood treated with citric acid - Tarasin, Manop; Rattanapun, Wigunda (Agriculture and Natural Resources, 2019)
Many termite species are major pests of wood products. Chemical and non-chemical wood preservatives are used to enhance the termite resistance of wood structures. A laboratory study using citric acid was used to test the protection of cajuputi wood (Melaleuca cajuputi; Myrtaceae) against Coptotermes gestroi Wasmann (Isoptera: Rhinotermitidae). Treated M. cajuputi wood was prepared using vacuum impregnation and alternatively by dipping. Dried M. cajuputi wood was dipped in 50%, 25% and 15% citric acid for 15 s, while the impregnation treatments involved 6%, 3% and 1.5% citric acid under 760 mmHg (101.33 kPa) pressure for 1 hr. The controls were M. cajuputi wood treated with 1.5% boron and non-treated wood. All cases were exposed to C. gestroi in no-choice experiments, and the relative mass loss of M. cajuputi wood that had been vacuum impregnated with citric acid was not significantly different from that impregnated with 1.5% boron, with both remaining below 11%. In all dipping treatments, the mass loss of M. cajuputi wood was higher than that with the baseline boron treatment.